Comparing the Effect of Structured Physical Games, Sports Vision Training, and Spark on the Components of Motor Skills in Children Aged 8 to 10 - Ghaneie Chegeni , Somayeh; Meshkati, Zohreh; Zahedi, Hamid; Badami, Rokhsareh (Iranian Journal of Neurodevelopmental Disorders, 2025)
Purpose: The purpose of this study was to compare the effects of different motor interventions, including structured physical games, the Spark program, and sports vision training, on improving motor skills in children.Methods and Materials: This research is a quasi-experimental study with a pretest-posttest design and a control group. The study population consisted of female elementary school students (age: 8.81 ± 0.77 years, height: 134.40 ± 7.97 cm, weight: 35.28 ± 8.77 kg) from Region One of Khorramabad City who were enrolled in the 2023-2024 academic year. The participants were 72 children aged 8 to 10 years, randomly assigned to four groups of 15 (structured physical games, Spark program, sports vision training, and control). The short form of the Bruininks-Oseretsky Test of Motor Proficiency was used to measure the components of motor skills. The structured physical games program was adapted from Al-Harndoon and Roberts (2020). The Spark program utilized the protocol of Moghaddamloo et al. (2014) and Mati' et al. (2017). The sports vision training protocol was based on the study of Clark et al. (2020). Data analysis was conducted using ANCOVA, and Bonferroni post-hoc tests were applied for pairwise comparisons of groups via SPSS software at a significance level of p < 0.05.Findings: The results indicated that structured physical games had a more significant effect on speed, agility, balance, bilateral coordination, and muscular strength compared to other groups (p > 0.05). The Spark group also showed improvements in some skills, but its performance in specific components such as speed and agility was lower than that of the structured physical games group. Sports vision training demonstrated limited effects and showed no significant differences from the control group in most skills.Conclusion: Overall, the findings emphasize the importance of designing structured, purposeful, and challenging exercises to enhance motor skills in children.